Biomimetic Diels–Alder Reactions in Natural Product Synthesis: A Personal Retrospect - Liu, Jingchun; Xi, Shuang; Tang, Yefeng (Synlett, 2022)
Nature has been recognized for her super capability of constructing complex molecules with remarkable efficiency and elegancy. Among nature’s versatile synthetic toolkits, Diels–Alder reaction is particularly attractive since it allows for rapid generation of molecular complexity from simple precursors. For natural products biosynthetically formed through Diels–Alder reactions, the most straightforward way to access them should build on biomimetic Diels–Alder reactions. However, the implementation of biomimetic Diels–Alder reactions in a laboratory setting may encounter considerable challenges, particularly for those suffering from complicated reactivity and selectivity issues. Indeed, the translation of a biosynthetic hypothesis into a real biomimetic synthesis entails the orchestrated combination of nature’s inspiration and chemist’s rational design. In this Account, we will briefly summarize our recent progress on the application of biomimetic Diels–Alder reactions in natural product synthesis. As shown in the discussed stories, rational manipulation of the structures of biosynthetic precursors plays a crucial role for the successful implementation of biomimetic Diels–Alder reactions.1 Introduction2 Biomimetic Synthesis of Rossinone B3 Biomimetic Synthesis of Homodimericin A4 Biomimetic Synthesis of Polycyclic and Dimeric Xanthanolides5 Biomimetic Synthesis of Periconiasins and Pericoannosins6 Biomimetic Synthesis of Merocyctochalasans7 Conclusion and Outlook
Keywords: Diels–Alder reaction; natural product; biomimetic synthesis; reactivity; selectivity